2021
DOI: 10.1542/peds.2020-029520
|View full text |Cite
|
Sign up to set email alerts
|

Demodex Folliculitis and Recent Dupilumab Administration

Abstract: Two adolescent boys presented with acute acneiform eruptions in the setting of recent dupilumab administration. Subsequent investigation via direct scraping of pustules revealed live Demodex mite colonization of the face. These adolescent patients represent a population not commonly associated with Demodex folliculitis, and we theorize their baseline commensal Demodex mite population may have increased as a consequence of dupilumab-induced, focused immunomodulation. We recommend that pediatricians consider Dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Thus, the use of dupilumab in AD patients has been associated with uncommon rosacea-like inflammation with demodex mite colonization. [15][16][17][18][19][20] Interestingly, paradoxical psoriasis-like skin reaction has also been observed during dupilumab therapy, a condition that shows IL-17 skew similar to rosacea and acne. [21][22][23] Collectively, facial skin of AD patients seems to be fundamentally different from the skin of patients with inflammatory disease in other organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the use of dupilumab in AD patients has been associated with uncommon rosacea-like inflammation with demodex mite colonization. [15][16][17][18][19][20] Interestingly, paradoxical psoriasis-like skin reaction has also been observed during dupilumab therapy, a condition that shows IL-17 skew similar to rosacea and acne. [21][22][23] Collectively, facial skin of AD patients seems to be fundamentally different from the skin of patients with inflammatory disease in other organs.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is reminiscent of the facial redness (and ocular surface problems) that is observed in some patients with AD following treatment with dupilumab, but not in patients with asthma and chronic rhinosinusitis with nasal polyps. Thus, the use of dupilumab in AD patients has been associated with uncommon rosacea‐like inflammation with demodex mite colonization 15–20 . Interestingly, paradoxical psoriasis‐like skin reaction has also been observed during dupilumab therapy, a condition that shows IL‐17 skew similar to rosacea and acne 21–23 .…”
Section: Discussionmentioning
confidence: 99%
“…41 Colonisation with demodex mites and concomitant IL-17 increase has also been hypothesised to play a role in OSDs in association with dupilumab. 42,43 Staphylococcus aureus has been suspected to play a role in the aetiology of OSDs in AD patients. 19,44 A recent study showed that AKC patients have a higher percentage of staphylococci in their conjunctival microbiome compared to controls, but the species remained not differentiated.…”
Section: Discussionmentioning
confidence: 99%
“…Th2 immunity is activated in response to both allergens and parasitic infections [48]. In recent years, cases of rosacea-like lesions have been reported in patients following the use of dupilumab [49, 50]. Live Demodex mites’ colonization of the face was discovered after further study by direct scraping of pustules [50].…”
Section: Discussionmentioning
confidence: 99%